1996
DOI: 10.1093/infdis/173.5.1157
|View full text |Cite
|
Sign up to set email alerts
|

A Noncovalent Complex Vaccine Prepared with Detoxified Escherichia coli J5 (Rc Chemotype) Lipopolysaccharide and Neisseria meningitidis Group B Outer Membrane Protein Produces Protective Antibodies against Gram-Negative Bacteremia

Abstract: Earlier studies showed that purified IgG from sera of rabbits immunized with a boiled Escherichia coli J5 (Rc chemotype) whole cell vaccine protected neutropenic rats against gram-negative bacterial sepsis. In the present study, de-O-acylated J5 lipopolysaccharide (J5 DLPS) as a noncovalent complex with Neisseria meningitidis group B outer membrane protein (GBOMP) elicited anti-J5 LPS antibodies in rabbits. IgG prepared from immune rabbit sera protected neutropenic rats against lethal challenge with Pseudomona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…In addition, it has been difficult to directly demonstrate substantial increased binding to LPS from heterologous gram-negative bacteria by the immunoglobulins in polyclonal antiserum to E. coli J5 [7,8]. Perhaps the strongest evidence that anti-LPS antibody might be involved comes from experiments in which passive immunization with immunoglobulin directed against a vaccine consisting of deacylated E. coli J5 LPS protected in a neutropenic model of sepsis [20]. Nonetheless, although antisera raised to heat-killed rough strains have been reported to protect, the exact mechanism by which this protection occurs remains elusive [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been difficult to directly demonstrate substantial increased binding to LPS from heterologous gram-negative bacteria by the immunoglobulins in polyclonal antiserum to E. coli J5 [7,8]. Perhaps the strongest evidence that anti-LPS antibody might be involved comes from experiments in which passive immunization with immunoglobulin directed against a vaccine consisting of deacylated E. coli J5 LPS protected in a neutropenic model of sepsis [20]. Nonetheless, although antisera raised to heat-killed rough strains have been reported to protect, the exact mechanism by which this protection occurs remains elusive [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, the increments in binding were highly variable; almost half of the bacterial strains exhibited negligible increments in binding and inexplicably, the J5 IgG fraction bound to 11.6% of viable J5 organisms, in contrast to 44.3% of the P. aeruginosa serotype 6 challenge strain. 155 Davis et al reported that J5 rabbit antiserum was capable of binding to LPS from group A, B, and C meningococci, as assessed by an HA assay.Z8 Meningococcal (as well as other neisserial) LPS do not possess 0 polysaccharide side chains. Rather, they are comparable to the unencumbered R-form LPS in rough-mutant enterobacteria and possess both group-specific and more broadly reactive epitopes.…”
Section: Rough-mutant Vaccines: Historical Perspectivementioning
confidence: 99%
“…However, an ideal vaccine candidate should not be limited to these immunization routes. Moreover, a general reduction of endotoxicity to minimize adverse effects might be necessary for a safe application of the OMV vaccine candidate in humans, as highlighted by a variety of other vaccine candidates containing LPS (47)(48)(49)(50)(51)(52)(53)(54)(55). For example, the Neisseria meningitidis OMV vaccines, used to control outbreaks in Scandinavia and New Zealand, include an additional step to remove most of the LPS by detergent extraction (56,57).…”
mentioning
confidence: 99%